Pengaruh Kerjasama Tim Dan Komunikasi Terhadap Kinerja Pegawai Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Palembang - Ilham, Firgi Anto; Agustian, Wiwin (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to examine the impact of teamwork and communication on the performance of employees at the Palembang City Investment and One-Stop Integrated Service Agency (DPMPTSP). The research adopts a quantitative approach, with the subjects being employees at the Palembang City Investment and One-Stop Integrated Service Agency. The sampling technique used is saturated sampling, involving 87 respondents. Data were collected through questionnaires distributed to the respondents. Data analysis techniques include validity and reliability tests, multiple linear regression analysis, t-tests, F-tests, and the determination test, conducted using SPSS. The results indicate a positive effect of the teamwork variable on employee performance. Additionally, communication has a positive influence on employee performance, and there is a positive correlation between teamwork and communication in relation to employee performance. Based on these findings, the study recommends enhancing teamwork and communication among employees to further improve performance at the Palembang City Investment and One-Stop Integrated Service Agency (DPMPTSP) in the future.